Methods for qualitative and quantitative analysis of pain and quality of life validated in Brazil: systematic review - Leandro Júnio MASULO; Marcela Lopes Silva MARTINS; Davidson Ribeiro COSTA; Renata Amadei NICOLAU (Faculdade São Leopoldo Mandic, 2019)
Objective: The need to quantify pain and quality of life (QoL) is essential for professionals considering their therapeutic approach. The goal of this review is to identify the methods to perform qualitative and quantitative analysis of pain and QoL validated in Brazil. Methods: Review by the LILACS, SciELO, MedLine and Google Scholar databases with the descriptors: methods, qualitative analysis, quantitative analysis, pain and quality of life. Inclusion criteria: articles published in Portuguese and in English in the period from 1996 to 2015. Exclusion criteria: incomplete texts, articles that did not address the subject of study and duplicate articles in the databases. Results: After applying the eligibility criteria, 27 articles were selected for reading, being that one article was excluded by presenting irrelevant result and another was excluded by duplication. From the 25 articles, one was published in 2015, three in 2014, one in 2013, three in 2012, five in 2011, two in 2010, three in 2009, four in 2008, two in 2004 and one in 1996. In relation to the studies, nine were clinical trials, 10 systematic reviews, five cross-sectional studies and one essay. Conclusion: The most frequently methods applied are the VAS and the McGill's Questionnaire, considering the multidimensional pain assessment. The most commonly used questionnaire to evaluate QoL is the SF-36. There is great difficulty to classify methods for assessing pain and QoL (qualitative or quantitative methods), since many authors report the same method when addressing the two interfaces.